ANALISIS IMPLEMENTASI KEBIJAKAN INSENTIF SITASI UNESA DALAM MENINGKATKAN SKOR INDIKATOR EXCELLENCE PADA PERINGKAT WEBOMETRIC UNIVERSITAS NEGERI SURABAYA - Cahya Dwi Novitasari; Ahmad Abdullah Zawawi (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of the citation incentive policy at Universitas Negeri Surabaya (UNESA) to enhance the excellence indicator score in the Webometric ranking. The Webometric ranking serves as a key indicator for assessing the quality and digital reputation of universities nationally and internationally. The research employed a qualitative descriptive method with a case study approach, including in-depth interviews, participatory observation, and documentation. Findings indicate that the implementation of the citation incentive policy has been effective, providing financial motivation that positively impacts the quantity and quality of faculty publications. Challenges include faculty time management, low-quality journals, and complex administrative procedures. UNESA demonstrates strong commitment supported by regulations, systematic management, and adequate research facilities as supporting factors. Faculty perceptions toward the policy are generally positive, especially concerning the OLOS and OLOD programs that encourage research productivity. The mechanisms of socialization, monitoring, and evaluation are continuously conducted through digital systems. The study recommends enhancing international training, simplifying administrative processes, and strengthening global collaboration to improve research quality and UNESA’s position in the Webometric ranking